1999
DOI: 10.1136/emj.16.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Excessive morphine requirements after pre-hospital nalbuphine analgesia.

Abstract: Nalbuphine hydrochloride is an opioid agonist-antagonist that has gained acceptance as a pre-hospital analgesic agent. Nalbuphine has equal analgesic properties to morphine, has a low addiction potential, and can be stored and administered without restrictions, unlike morphine. To date no clinical evidence has been published to support the theoretical difficulty that the action of opioids administered after nalbuphine could be altered or negated. The foliowing case reports highlight 10 patients who received na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 9 publications
3
11
0
Order By: Relevance
“…This has been reported in a previous study, 14 although others have not observed this effect. 15 16 In conclusion, a rapid dosing regimen of nalbuphine is more effective than and equally as safe as a cautious regimen.…”
Section: Discussionsupporting
confidence: 79%
“…This has been reported in a previous study, 14 although others have not observed this effect. 15 16 In conclusion, a rapid dosing regimen of nalbuphine is more effective than and equally as safe as a cautious regimen.…”
Section: Discussionsupporting
confidence: 79%
“…14 Some researchers have voiced concerns about the use of nalbuphine by paramedics, especially the potential for delay at the scene 15 and the possibility of antagonism of other opioids, should further analgesic therapy be required after arrival at hospital. 16 However, other authors have not observed these effects. 17 18 Nalbuphine's manufacturers recommend a dosing regimen of 10 mg to 20 mg for a 70 kg patient.…”
Section: Introductionmentioning
confidence: 95%
“…Authors have previously expressed concerns over the potential of nalbuphine to increase requirements of opiate analgesics after arrival at hospital due to its partial antagonist effect 5 6. The potential for nalbuphine to produce withdrawal in opiate dependent people has been explored in a study using opiate dependent volunteers, where it was found that the withdrawal syndrome precipitated by nalbuphine was indistinguishable from that produced by giving naloxone 7.…”
Section: Discussionmentioning
confidence: 99%